Serious Mental Illness in Nursing Homes: Stakeholder Perspectives on the Federal Preadmission Screening Program. Issue 5 (3rd September 2022) - Bucy, Taylor; Moeller, Kelly; Skarphol, Tricia; Shippee, Nathan; Bowblis, John R.; Winkelman, Tyler; Shippee, Tetyana
ABSTRACT: The federal Preadmission Screening and Resident Review (PASRR) program was enacted in the 1980s amid concerns surrounding the quality of nursing home (NH) care. This program is meant to serve as a tool to assist with level of care determinations for NH applicants with serious mental illness (SMI) and was intended to limit the growth in the number of NH residents with SMI. Despite this policy effort, the prevalence of SMI in NHs has continued to increase, and little is known about the mechanisms driving the heterogeneous and suboptimal administration of the PASRR program, absent routine evaluative efforts. We conducted 20 semi-structured interviews with state and national stakeholders to identify factors affecting PASRR program administration and NH care for residents with SMI. Stakeholders expressed concern regarding fragmentation, specifically lack of clarity in the value of assessments beyond a regulatory requirement. Additionally, they cited variable program administration as contributing to fragmented communication patterns and inconsistent training across jurisdictions. Given the number of people with SMI currently residing in NHs, policy and practice should take a person-centered approach to assess how PASRR can be better used to support resident needs.